Growth Induction of Cavendish Buds (Musa Acuminata L.) on Difference Concentration of IBA and BA in Vitro - M, Subandi; Jannata, Arkhan; Hasani, Sofiya (Asian Journal of Agriculture and Rural Development, 2019)
The propagation of Cavendish (Musa acuminata L.) seedling conventionally relatively took a longer time, not uniformed in quality and possibly has a disease that is derived from unhealthy mother stock. This research aimed to find the effect of IBA and BA on difference concentrations on the growth of plantlet, also to determine the optimum concentration of IBA and BA on the growth of Cavendish bud plantlets in vitro. This research had been carried out started from April to July 2018 in Tissue Culture Laboratory, Research Institute of Horticultural Seed Development of Pasir Banteng, Sumedang, West Java. Indonesia. The method used in this research was Completely Randomized Design with two factors. The first factor was IBA (i0 = 0 mg L-1, i1= 0,75 mg L-1, dan i2= 1,5 mg L1), and the second factor was BA (b1= 1 mg L-1 b2= 3 mg L-1 b3= 5 mg L-1 b4= 7 mg L-1), replicated three times. Duncan Multiple Range Test (DMRT) was used as a further test. The result showed an interaction between IBA and BA on the parameters of shoot growth and the number of leaves at 6 WAC. IBA showed an independent effect on the number of buds. The addition of 1,5 mg L-1 IBA and 3 mg L-1 BA was optimum for the growth of Cavendish bud explants.